Has the minimum wage policy been important for reducing poverty in Brazil? A decomposition analysis for the period from 2002 to 2013 - Alessandra Scalioni Brito; Celia Lessa Kerstenetzky (EconomiA, 2019)
This study aims to analyze the contribution of the minimum wage valorization policy to the reduction in poverty that occurred in the first decade of the 21st century in Brazil, considering not only the incidence of poverty but also its intensity and severity. A decomposition methodology was used to isolate the marginal contribution of the minimum wage in the observed changes, taking into account the roles of setting the values of basic pension and social assistance benefits (the Benefício de Prestaç\~ao Continuada or BPC) in addition to setting the wage floor. Between 2002 and 2013, the minimum wage contributed to a 38.2% reduction in the proportion of impoverished people, a 39.4% reduction in the intensity of poverty and 40.6% decrease in the severity of poverty. Our results also reveal geographic differences, with the minimum wage being more important in the poorest regions.
Keywords: H53; H55; I32; J31; 330; Decomposition; Minimum wage; Poverty; Social security